Incompatibilities of crimes against humanity in relation to the crimes of enforced disappearance and torture - Guarnizo Miranda, Betty Leonor (2024)
The present research aims to address the issues arising from the inclusion of crimes against humanity within the realm of international law, thus confronting domestic law. This scenario has caused tensions with the principle of legality, recognized as a fundamental right and guiding principle whose primary purpose is to restrict the state's ability to impose penalties within the internal Peruvian penal system. The legal maxim establishing the presumption of innocence until proven guilty constitutes the foundation of this principle, where the classification of an act as a crime is essential for its consideration as such. Another crucial aspect of this principle is the preservation of legality, evident in the lack of typification of the actions undertaken in prosecution. The prohibition of retroactive application of the law, known as lex praevia, represents an additional guarantee to prevent a person from being sanctioned for actions taken before the norm was incorporated into the legal system. Certainty in tax obligations, also identified as lex certa, constitutes another fundamental component of this principle, ensuring that criminal law sufficiently defines prohibited acts so that the average citizen can clearly understand what is prohibited by law.